Electrolytes based on N‐Butyl‐N‐Methyl‐Pyrrolidinium 4, 5‐Dicyano‐2‐(Trifluoromethyl) Imidazole for High Voltage Electrochemical Double Layer Capacitors. Issue 2 (7th November 2018) - Scalia, Alberto; Varzi, Alberto; Moretti, Arianna; Ruschhaupt, Peter; Lamberti, Andrea; Tresso, Elena; Passerini, Stefano
Abstract: Owing to their exceptional electrochemical stability, ionic liquids (ILs) are highly promising electrolytes for high voltage electrochemical double layer capacitors (EDLCs). However, these molten salts often suffer from high viscosity and low conductivity, strongly affecting their application at room temperature. In this work the potential role of N‐butyl‐N‐methyl‐pyrrolidinium 4, 5‐dicyano‐2‐(trifluoromethyl) imidazole (Pyr14 TDI) as electrolyte component is evaluated for the first time. Although it is classified as an IL, its melting point at 48 °C hinders the use of the pure IL as solvent‐free electrolyte at medium‐to‐low temperatures. For this reason, mixtures with propylene carbonate (PC) are investigated to widen its temperature operation range (−30 to 60 °C). Different Pyr14 TDI:PC ratios are investigated, from diluted solution (1 : 3 w/w) to solvent‐in‐salt (3 : 1 w/w). The properties of such electrolytes are determined in terms of viscosity, density, flash point, ionic conductivity, and electrochemical performance in EDLC. By proper electrode balancing, a maximum cell voltage of 3.3 V is achieved in case of PC:Pyr14 TDI (1 : 3). However, despite the voltage limitation to 3 V, the highest specific energy and power values are obtained with the most diluted solution (3 : 1). Abstract : Binary mixtures of N‐butyl‐N‐methyl‐pyrrolidinium 4, 5‐dicyano‐2‐(trifluoromethyl) imidazole (Pyr14 TDI) and propylene carbonate (PC) are studied as electrolytes for high voltage electrochemical double layer capacitors (EDLC). By tuning the composition of the solution, extended liquid range and conductivity can be achieved. A maximum cell voltage as high as 3.3 V and promising stability represent a substantial improvement compared to current state‐of‐the‐art EDLC electrolytes.